2009
DOI: 10.1186/1741-7015-7-41
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated ERK is a potential predictor of sensitivity to sorafenib when treating hepatocellular carcinoma: evidence from an in vitrostudy

Abstract: Background: Sorafenib is the first agent that has demonstrated an improved overall survival benefit in advanced hepatocellular carcinoma (HCC), setting a new standard for first-line treatment. However, no one has yet been able to predict sensitivity to sorafenib. Pre-treatment pERK level has been shown to be associated with favorable response to such therapy in a phase II clinical study, indicating that pERK may be a potential biomarker for treatment of HCC with sorafenib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
108
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 20 publications
7
108
0
Order By: Relevance
“…Therefore, it is important to identify the best prognostic factors that can predict response to sorafenib. Certain studies showed that serum VEGF concentration and extracellular signal-regulated kinase levels were good predictors (26,27); however, other surrogate biomarkers must be explored to evaluate prognosis or the efficacy of treatment with sorafenib HCC. In the present study, the patients were restricted to those with BCLC stage C or BCLC stage B but who had previously experienced TACE failure, for whom sorafenib is the major treatment method (28).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to identify the best prognostic factors that can predict response to sorafenib. Certain studies showed that serum VEGF concentration and extracellular signal-regulated kinase levels were good predictors (26,27); however, other surrogate biomarkers must be explored to evaluate prognosis or the efficacy of treatment with sorafenib HCC. In the present study, the patients were restricted to those with BCLC stage C or BCLC stage B but who had previously experienced TACE failure, for whom sorafenib is the major treatment method (28).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that sorafenib inhibited the phosphorylated ERK (pERK) in HCC PLC/PRF/5 and HepG2 cells [9] . Zhang et al [12] reported that the effects of sorafenib on cell proliferation were significantly correlated with basal pERK levels and the U0126, a selective inhibitor of ERK1/2, could reduce the sensitivity of HCC cells to sorafenib through downregulation of pERK. In a phase Ⅱ clinical study of sorafenib, the pERK levels in tumor samples from 33 patients showed the correlation with median time to progress (TTP) [13] .…”
Section: Sensitivitymentioning
confidence: 99%
“…Biologic activities of sorafenib and regorafenib can be demonstrated in vitro within a few hours of exposure to 0.1-10 µM of the drugs [8][9][10][11][12][13]. The cytotoxicity is cell specific and includes alterations in multiple signaling pathways, execution of apoptosis, induction of ER stress, and inhibition of protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity is cell specific and includes alterations in multiple signaling pathways, execution of apoptosis, induction of ER stress, and inhibition of protein synthesis. At 5 to 50 µM, for example, sorafenib inhibited the proliferation of hepatocellular carcinoma cell lines; the degree of inhibition was dependent on pERK expression [10]. Exposure of human leukemia cells to 10 µM sorafenib produced cytotoxicity that involved inducing ER stress and generation of ROS [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation